PENGARUH LITERASI PASAR MODAL, INKLUSI PASAR MODAL DAN PERSEPSI RISIKO TERHADAP KEPUTUSAN INVESTASI SAHAM GENERASI Z DI PASAR MODAL (STUDI KASUS PADA GENERASI Z USIA 20-26 TAHUN DI 2024) - Damayanti, Khairiyah; Listiawati, Rodiana (Indonesian Journal of Economy, Business, Entrepreneuship and Finance, 2024)
The high interest in stock investment among investors in Indonesia is dominated by Generation Z. This is due to many factors such as capital market literacy, capital market inclusion, and risk perception. This can occur due to many factors such as capital market literacy, capital market inclusion, and risk perception. However, the 2022 National Survey of Financial Literacy and Inclusion data shows a decrease in the level of capital market literacy and an increase in the level of capital market inclusion. The existence of this imbalance can lead to inappropriate stock investment decision making. Then, there are differences in the results of previous studies regarding the risk perception variable on generation Z stock investment decisions. Therefore, this study aims to examine the effect of capital market literacy, capital market inclusion, and risk perception on generation z stock investment decisions in the capital market. This research is quantitative research and uses multiple linear regression tests with the help of the IBM SPSS 2.5 program. The data used is primary data distributed online and obtained 100 generation Z respondents aged 20-26 years. The results of this study are capital market literacy has no effect on generation Z's stock investment decisions in the capital market. While capital market inclusion, and risk perception have a significant influence on generation Z's stock investment decisions in the capital market.